Motif Perilaku Korea Utara Mengingkari Deklarasi Panmunjom Ditinjau dari Regional Security Complex Theory - Dewi Astuti Mudji; Tino Rila Sebayang; Fathira Iftihani Noor (Universitas 17 Agustus 1945 Jakarta, 2022)
This paper aims to find out the reasons for North Korea's behavioral motives for rejecting the Panmunjom Declaration. The Korean peninsula returned to a tense situation after North Korea violated several value agreements that threatened South Korea and regional security stability by continuing to test its nuclear weapons and blow up its liaison office in retaliation for South Korea's failure to prevent anti-North deployments. Korean propaganda from defector groups at the border. By using descriptive analytical research method with a qualitative approach, this paper uses primary and secondary data obtained from books, journals, articles, and official government and non-government documents. In addition, this paper uses the Regional Security Complex Theory, the concept of the National Interest, the theory of rationality in policy making. The results of this paper indicate that the motive for North Korea's behavior is to maintain the security of its country from threats from the United States and other countries and so that its country is considered a nuclear country whose position is equal to other countries and demands the lifting of the sanctions embargo. Moreover, the current state of tension is being used by North Korea to increase its influence in the dialogue